hukum keluarga islam Hukum Keluarga Islam Parenting Islami Sebagai Upaya Keberhasilan Mendidik Anak - Mihfa Rizkiya Mihfa (HKI IAI Miftahul Ulum Pamekasan, 2022)
Abstract The study of Hadhanah or now more often we hear as parenting is getting more interesting. Many parenting experts with various scientific backgrounds campaign for the procedures for educating children that continue to develop in this modern era. In Islam, the knowledge of children's education is discussed in the Hadhanah chapter, sourced from the Qur'an and the Sunnah of the Prophet. The right education of children will produce the desired generation for every parent. Islamic parenting certainly puts forward how to form a pious person and be on the straight path. This basic attitude is the first step to achieve success and success. The reality in the field we see that many parents are careless in educating their children. Does not want to upgrade his knowledge about the character of the child, the emotional needs of the child, and what supporting factors can make the child's education successful. Many parents are negligent in their duties, allowing children to play with gadgets as much as they want just so that children can sit still. Parents also tend to only entrust their children's education to teachers at school. So that children get a less than optimal education. Children become a pessimistic generation, their brains are empty, and their souls are dry from strong beliefs. Keywords: Parenting, Children and Islam Abstrak Kajian tentang Hadhanah atau kini lebih sering kita dengar sebagai parenting semakin menarik pembahasannya. Banyak pakar parenting dengan berbagai latar belakang keilmuannya mengkampanyekan tatacara mendidik anak yang terus berkembang di zaman modern ini. Dalam islam ilmu tentang pendidikan anak di bahas dalam bab Hadhanah bersumber dari Al-qur’an dan Sunnah Rasulullah. Pendidikan anak yang benar akan menghasilkan generasi dambaan bagi setiap orang tua. Parenting islami tentu mengedepankan bagaimana cara membentuk pribadi yang shalih dan berada pada jalan yang lurus. Sikap dasar tersebut sebagai langkah awal untuk meraih kesuksesan dan keberhasilan. Kenyataan dilapangan kita saksikan banyak orang tua yang teledor dalam mendidik anak nya. Tidak mau mengupgrade pengetahuannya tentang bagaimana karakter anak, kebutuhan emosional anak, dan fakto-faktor pendukung apa yang bisa menyukseskan pendidikan anak tersebut. Banyak orang tua lalai dalam tugasnya, membiarkan anak bermain gadget sepuasnya hanya agar anak bisa duduk manis. Para orang tua juga cenderung hanya mempercayakan pendidikan anak nya pada guru di sekolah. Sehingga anak mendapatkan pendidikan yang kurang maksimal. Anak menjadi generasi yang pesimis, otaknya kosong, dan jiwa mereka kering dari keyakinan yang kuat. Kata Kunci: Parenting, Anak dan Islam.